Analytical methods for isolation and identification of resin glycosides from Convolvulaceae family (Revista de Investigaciones Universidad del Quindío, 2013)
High-Performance Liquid Chromatography has been a powerful technique for purification from simple and complex molecules. Resin Glycosides has been isolated from convolvulaceae species and purified by Preparative- scale recycling HPLC. This paper has been written as an effort to contribute to the scientific knowledge about chemistry of resin glycosides, especially, purification techniques from some intact glycolipids by HPLC, as well as, the spectroscopic characteristics by Nuclear Magnetic Resonance and spectrometric details by fast-atom bombardment mass spectrometry (FABMS) and electrospray ionization (ESIMS), for the identification of these class of molecules.
Keywords: Convolvulaceae; Resin Glycosides; High Performance Liquid Chromatography; Nuclear Magnetic Resonance